Assassin's Creed e transmídia: convergências e jogabilidades - Ebert, Vagner (2017)
Storytelling has populated human culture in different ways for a very long time. With the advance in technology, new ways of creating and telling stories emerge and, among several nomenclatures, they are also known by the name of transmedia storytelling, a concept created by Henry Jenkins (2009) to designate a story that gets dispersed across multiple delivery channels, each of them making their contribution to the unfolding of the storytelling universe. Books, comics, movies, animations, games and so many others are some of the possibilities for building this type of technological storytelling that influences and alters reading strategies and the reader's profile as well. An example of this type of storytelling and corpora of this dissertation is the Assassin's Creed franchise, an electronic game that branched out to other delivery channels and other narratives, thus becoming a transmedia storytelling that is considered the basis for the problem of this study, which intends to find out how the transmedia interrelations are constructed and, consequently, the transmedia storytelling of the Assassin's Creed franchise. Based on this premise, this research investigates the transmedia storytelling and its possibilities of reading from the interrelations between ga mes, movies and books associated to the Assassin's Creed franchise, starting from the following objectives: a) to discuss, under different theoretical bases, the transmedia storytelling; b) reflect on the reading strategies in different transmedial productions; and c) to present the products of the Assassin's Creed franchise and its transmedial relations. In order to achieve the objectives mentioned here, we have the methodology based on the content analysis method, it was constructed in three stages: the first is an isolated analysis of each element, book, game, or film from the franchise that is investigated; The second is an analysis of the elements that interrelate within the different delivery channels; And, finally, the analysis of the work from the interrelations of its different supports and, therefore, as a transmedia narrative. This study is divided into 5 (five) chapters, the first three explore the theoretical foundations; the fourth describes the methodology and the fifth contains the consequent analysis of the corpora, in which it was possible to verify that the key elements that promote the interrelations are as important as the possibility of autonomous access for the construction of the transmedia storytelling.